When a linguistic variable doesn’t vary (much): The subjunctive mood in a conservative variety of Acadian French and its relevance to the actuation problem - Comeau, Philip (Journal of French language studies, 2020)
This study considers the subjunctive mood in one of the most conservative varieties of Acadian French, that spoken in the Baie Sainte-Marie region in the Canadian province of Nova Scotia. A number of claims made in the literature are considered: whether the subjunctive mood is undergoing loss, whether it expresses semantic meaning, and whether it is lexically-conditioned. Unlike most spoken varieties of French where the subjunctive is argued to be a linguistic variable (i.e., it varies with other moods), the results for Baie Sainte-Marie show that it varies very little. The analysis reveals that the few cases of variation can be accounted for by formal theoretical approaches to the subjunctive where this mood is argued to express modality. With limited variation, the subjunctive is not showing signs of loss. These findings suggest that the subjunctive is not part of a linguistic variable and so is not subject to inherent variability. I further argue that the retention of the imperfect subjunctive in this variety, along with a tense concordance effect, can help us understand why the subjunctive became a linguistic variable in other varieties of French, which ultimately contributes to our understanding of the actuation problem.